Temperature Effect on Rheological Behavior of Portuguese Honeys - Afonso Maria João; Magalhães Marta; Fernandes Luana; Castro Marina; Ramalhosa Elsa C.D. (Polish Journal of Food and Nutrition Sciences)
In the present work the temperature effect on rheological properties of Portuguese honeys was studied for the first time. Two unifloral honeys – heather and rosemary – and a polyflower honey were analyzed. All honeys showed flow independence over time and behaved as Newtonian fluids at the studied temperature and shear rate ranges. For all honeys it was found that the viscosity decreased with temperature and the rosemary honey was the one that always presented the lowest viscosity at 30°C (6120 mPa·s), 50°C (603 mPa·s) and 70°C (145 mPa·s). The temperature dependence of viscosity was well described by the K0×eAT-B$K_0 × e^{{A \over {T - B}}} $ equation. Nevertheless, good regression coefficients were also obtained when fitting the experimental data to the Arrhenius model, showing the rosemary honey to be less temperature sensitive. The results obtained in this study are of great interest to beekeepers and industrials that handle and prepare eatable honey-based products because they will be better informed about the best type of honey to use.